Informática na educação: o programa de informatização na rede pública de ensino (ProInfo) : o caso das escolas da rede estadual de ensino /Aracaju-SE - Conceição, Sheilla Silva da (2008)
This essay presents a study which has taken place in two public schools in Aracaju-SE on Educational Computing through a Computing Program in Education (ProInfo). Its main goal is to analyse wheather ProInfo is managing to improve skills such as authonomy and critical thinking in the learning process once they are required in the knowledge society. The methodology applied was participant observation (which allowed to realize the day by day at schools concerning computing lab usage) and semi-structured interview (for subjective answers allowed new questions in order to get deeper answers from the interviewees). This study was based on pedagogical and technological principles through theoretical and methodological categories that lead the usage of computing resources in the learning process. Educational computing is in the center of some discussions and this happens because we are living in the age of Information and knowledge where information tends to be the main source of development. Therefore, schools must priorize in their pedagogical proposals not only the conception but also the assessment of computing, hence the citzen must get a holistic education which engage TIC, through which, both students and teachers would learn meaningfully. In the schools where this study has taken place the usage of computers for pedagogical purposes has provided learning once students feel motivated to learn through this tool and also they have to cope not only with an insufficient number of computers but also lack of qualified teachers. This qualification must be urgent so that it will enable teachers to use the technology in education in a more critical and attractive way so that they will better mediate the learning process itself.